State, Globalization and Multilateralism
XVI, 188 p.
Keywords: This volume presents a reconsideration of the concepts of State and political power within the evolving multilateral network of cooperation and conflict. By means of an innovating research strategy, it explains state resilience within global and regional governance while deepening the transformation of the traditional sovereign state concepts, including by emerging powers. Rather than considering the EU as an isolated case study, the book considers the EU as both a reference and a proactive player, which fosters a new research agenda both for comparative studies on regional cooperation and political theory. Lastly, in view of the currently emergent, unprecedented and asymmetrical, ‘multi-polar’ world, and of several forms of continent and instrumental multilateral cooperation, it considers the need for putting regionalism and democratic legitimacy at the very core of a normative and institutionalist research agenda for a ''new multilateralism''.